Telaah Literatur : Pemberian Asi Dan Ibu Bekerja - Riri Novayelinda (Fakultas Keperawatan, Universitas Riau, 2012)
There are many studies investigates about breastfeeding in working mother in English literature. However the number of literaturereview written in Indonesian is still limited. The aim of this study is to identify the obstacles in breastfeeding for working motherby using the systematic review approach. The articles were search by using electronic data base including CINAHL, Medline,PsychInfo, Proquest, Blackwell Science and Science Direct by in Indonesian and English by using the keywords breastfeeding,employed women, working mothers, working women. The years were limited between 1987 and 1997. This study found that theworking condition doesn’t have any impact on breastfeeding initiation but it influences the duration of breastfeeding. Workingmother need facility and policy supports from employers in order to maintain breastfeeding and working as well as the personalsupport from co workers and families. Lack of supports from health care workers and type and locations of workplace wereindentified as the obstacles for breastfeeding.Keywords: Breasfeeding, working mother’s